Photodynamic therapy with a novel photosensitizer inhibits BLM-induced pulmonary fibrosis in mice via MRC1-mediated pathway - Zhu, Minghui; Wang, Nan; Zhang, Feiyu; Rong, Yumei; Zhao, Zhenyu (Frontiers in Pharmacology, 2025)
BackgroundPulmonary fibrosis (PF) is a devastating interstitial lung disease with limited therapeutic options, characterized by progressive extracellular matrix deposition and irreversible functional decline. Photodynamic therapy (PDT) represents a promising therapeutic modality, but its application in PF is hindered by the lack of effective and safe photosensitizers. This study aimed to investigate the therapeutic potential and underlying mechanisms of a novel photosensitizer, LD4, in a murine model of PF.MethodsThe anti-fibrotic efficacy of PDT-LD4 was evaluated both in vitro using human embryonic lung fibroblasts (HELF) and in vivo in a bleomycin (BLM)-induced pulmonary fibrosis model in mice. Mice were randomly allocated into control, model (BLM), pirfenidone (PFD, positive control), and three PDT-LD4 dose groups (60, 120, and 240 μg/kg). Treatments were administered weekly via intratracheal instillation followed by thoracic irradiation (650 nm, 25 J/cm2). Assessments included survival rate, histopathology, inflammatory cytokine levels (IL-1β, IL-6, TNF-α), oxidative stress markers (SOD, GSH, MDA, ROS), collagen deposition (Collagen I/III immunohistochemistry, hydroxyproline content), label-free quantitative proteomics, and molecular docking.ResultsPDT-LD4 significantly inhibited HELF proliferation while exhibiting low dark toxicity. In BLM-induced mice, PDT-LD4 markedly improved survival rates and attenuated body weight loss. Histopathological analysis demonstrated that PDT-LD4 substantially reduced inflammatory infiltration and collagen deposition. Mechanistically, PDT-LD4 suppressed pro-inflammatory cytokine levels, alleviated oxidative stress by restoring antioxidant capacity, and inhibited collagen synthesis. Proteomic profiling identified macrophage mannose receptor (MRC1) as a differentially expressed protein, whose BLM-induced upregulation was reversed by PDT-LD4, suggesting that the regulation of pulmonary fibrosis (PF) may involve the modulation of MRC1. Molecular docking confirmed a stable binding interaction between LD4 and MRC1. Importantly, systemic toxicity assessment revealed no significant damage to major organs.ConclusionPDT-LD4 exerts anti-fibrotic effects in bleomycin-induced pulmonary fibrosis through multiple mechanisms including anti-inflammation, anti-oxidation and anti-fibrosis, which may be related to the regulation of MRC1. Given its proven efficacy and good safety, PDT-LD4 emerges as a promising novel therapeutic strategy and is worthy of further clinical research for pulmonary fibrosis.